2018
DOI: 10.4103/ijccm.ijccm_49_18
|View full text |Cite
|
Sign up to set email alerts
|

The platelet count and its implications in sickle cell disease patients admitted for intensive care

Abstract: Background and Aims:In sickle cell disease (SCD) patients admitted for intensive care, evaluation of platelet counts in different types of sickle cell complications and its prognostic relevance are not well-studied. Illuminating these aspects were the objectives of this study.Materials and Methods:A chart review of 136 adult SCD patients consecutively admitted to our Intensive Care Unit (ICU) was done. The prognosis on day 1 was assessed by Acute Physiology and Chronic Health Evaluation (APACHE II) and multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
(47 reference statements)
0
13
0
1
Order By: Relevance
“…Also, sickle cellendothelial interaction results in coagulation factor activation and a state of compensated disseminated intravascular coagulation with platelet consumption. 13 The median Serum creatinine level reported in the study was 0.6200 mg/dl in group A participants and 0.7600 mg/dl amongst group B participants. The range varied from 0.50 to 0.90 mg/dl in control group.…”
Section: Frequency Of Blood Transfusionmentioning
confidence: 63%
See 1 more Smart Citation
“…Also, sickle cellendothelial interaction results in coagulation factor activation and a state of compensated disseminated intravascular coagulation with platelet consumption. 13 The median Serum creatinine level reported in the study was 0.6200 mg/dl in group A participants and 0.7600 mg/dl amongst group B participants. The range varied from 0.50 to 0.90 mg/dl in control group.…”
Section: Frequency Of Blood Transfusionmentioning
confidence: 63%
“…11 Shanley et al, (2011) also studied the usefulness of platelet count as a predictor of VOC amongst SCD patients and reported larger decline in platelets count in them. 12 Shome DK et al, (2018) suggested the mechanism to explain alteration in platelet count in SCD. They suggested that direct correlations of platelet counts with WBC and reticulocytes found in their study suggest that compromised marrow function is a contributory factor.…”
Section: Frequency Of Blood Transfusionmentioning
confidence: 99%
“…A rare consequence of sickle cell illness is a spontaneous extradural hematoma. The formation of extradural hematomas in SCD has been linked to unestablished pathophysiologies like vaso-occlusion of the hematopoietic calvarial diploic bone resulting in bone infarction and blood leaking into the periosteal, epidural, and sub-galeal regions [2,7]. Acute and rapid increase in hematopoiesis, resulting in microfracture of the already thin inner cortex and blood and hematopoietic tissue extravasation with sludging of sickle cells in the diploic veins, obstructing venous drainage, and causing blood leaking due to vascular injury have also been postulated.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to WBC and platelet counts, we found significant increase in the total corrected WBC and platelets which are not unusual in SCA status. The majority of studies performed on SCA patients have shown significant increases in the total counts since the disease is characterised by active inflammation and haemolysis, which trigger continuous production of WBC and platelets resulting in high peripheral counts [18][19][20][21][22][23][24]. A previous study performed on SCA patients to evaluate the laboratory markers during steady states of the disease found that increased emergency department utilisation was significantly associated with elevated steady-state counts of WBC and platelets (p \ 0.001).…”
Section: Discussionmentioning
confidence: 99%